Romain Debref, Le processus d’innovation environnementale face à ses contradictions : le cas du secteur des revêtements de sol résilients - Romain Debref (Revue de la Régulation)
This thesis questions the relevancy of the process of environmental innovation in the sector of the resilient flooring in Europe facing to the challenge of sustainability. Even if technical progress might be observed as starting point, we assume this process and its concepts are also taken over by industrial groups to withstand environmental controversies. This work points out two issues. From a theoretical point of view, the difficulty of identifying what are environmental innovations. From a empirical point of view, how practitioners interprets concepts and uses dedicated-tools.